Revitalisasi Madrasah di Wilayah Eksplorasi dan Eksploitasi Migas Blok Cepu - Huda, M. Nuril (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2016)
The article explains madrasah empowerment actions through a set of assistance processes at MI (Islamic elementary school) Uyunul Ulum and MTs (Islamic secondary school) Bahrul Ulum in the Village of Gayam in Bojonegoro. Through participatory action research approach, the process of assistance is intended to: 1) identify the impact of oil and gas exploration and exploitation towards the existence of madrasah in the Cepu Block; 2) formulate an appropriate model of madrasah empowerment in the oil and gas exploration area; 3) implement the appropriate assistance processes of madrasah empowerment in the area. The assistance processes cover a number of activities such as focused group discussion with the local communities, workshop of madrasah development, and facilitating activities for teachers and educational administrative staff members. The assistance has brought about the following results: 1) oil and gas exploration and exploitation have resulted in significant impact towards economic, cultural, and circumstantial changes; 2) madrasah plays a strategic role to create excellent generation based on Islamic values; 3) madrasahâs capacity should be strengthened in order to create outstanding human resource, curriculum, and means of education; 4) the assistance process should be continuously maintained in order to assure and increase the quality of madrasah.